Assessing Author Identifiers: Preparing for a Linked Data Approach to Name Authority Control in an Institutional Repository Context. Issue 1 (3rd April 2019) - Downey, Moira
Abstract: Linked data solutions for name authority control in digital libraries are an area of growing interest, particularly among institutional repositories (IRs). This article first considers the shift from traditional authority files to author identifiers, highlighting some of the challenges and possibilities. An analysis of author name strings in Duke University's open access repository, DukeSpace, is conducted to identify a suitable source of author URIs for Duke's newly launched repository for research data. Does one of the three prominent international authority sources—Library of Congress Name Authority File (LCNAF), Virtual International Authority File (VIAF), and Open Researcher and Contributor Identifier (ORCID)—demonstrate the most comprehensive uptake? Finally, recommendations surrounding a technical approach to leveraging author Uniform Resource Identifiers (URIs) at Duke are briefly considered.